Fundamental Determinants of Stock Returns: Evidence from Property and Real Estate Companies - Muhammad Rofi'i (UPY Business and Management Journal (UMBJ), 2026)
Purpose: This study aims to examine the impact of key financial indicators on stock returns of property and real estate companies during the 2020Q2–2024Q4 period. The research seeks to identify which financial ratios most strongly influence market valuation in a sector characterized by high capital intensity and cyclical demand, particularly during the post-pandemic recovery phase. Methodology: The study adopts a quantitative approach using secondary panel data from ten listed companies. Multiple linear regression analysis with the Random Effect Model (REM) was applied using Eviews. Findings: The results indicate that leverage has a negative and significant effect on stock returns, implying that higher debt exposure increases financial risk and weakens investor sentiment. In contrast, profitability shows a positive and significant relationship, suggesting that greater equity efficiency enhances profitability and investor confidence. Liquidity and Market Value exhibit no significant impact, indicating that short-term liquidity and per-share earnings are less influential in determining stock performance in this sector. These findings confirm that investors in property and real estate prioritize risk management and capital efficiency over temporary liquidity or earnings fluctuations. Originality: This study contributes to the literature by incorporating both the Covid-19 downturn and recovery periods, providing updated empirical evidence on how financial ratios serve as market signals consistent with signaling theory and capital structure theory in emerging markets. Research limitations: The limited sample size and sector-specific scope may constrain generalizability to other industries. Practical implications: The results highlight the strategic importance of prudent leverage management and efficient equity utilization for maintaining investor trust and sustaining long-term stock performance.